What is beautiful brings out what is good in you: The effect of facial attractiveness on individuals' honesty. (17th September 2015) - Wang, Jing; Xia, Tiansheng; Xu, Liling; Ru, Taotao; Mo, Ce; Wang, Ting Ting; Mo, Lei
Abstract : This study tested whether the presence of an attractive face would influence individuals' honesty. In 2 experiments, 225 participants were asked to predict the outcome of computerised coin‐flips and to self‐report the accuracy of their predictions. Self‐reports were made in the presence of a facial photo of a female who had been rated before the experiment as high attractive, middle attractive or low attractive by other volunteers. Participants were rewarded based on their self‐reported (not actual) accuracy. The results showed that subjects tended to give more dishonest self‐reports when presented with middle or low attractive facial images than when presented with high attractive images, with self‐reported accuracy being significantly higher than the random level. The results of this study show that presented with an attractive face, subjects tend to engage in behaviours that conform to moral codes.